Diagnostic accuracy of lung ultrasonography combined with procalcitonin for the diagnosis of pneumonia: a pilot study - Peiman Nazerian; Gabriele Cerini; Simone Vanni; Chiara Gigli; Maurizio Zanobetti; Maurizio Bartolucci; Stefano Grifoni; Giovanni Volpicelli (Critical Ultrasound Journal, 2016)
Abstract Background The diagnostic value of lung ultrasonography (LUS) and procalcitonin (PCT) in the diagnosis of lung infections is known. No studies evaluated the combination of LUS and PCT for the diagnosis of pneumonia in the emergency department (ED). We evaluated the diagnostic accuracy of the combination of LUS and PCT in the diagnosis of pneumonia. Methods Patients with respiratory symptoms of unexplained origin who underwent a chest CT in ED were included in the study if PCT assay was available. LUS was performed before CT and was targeted to the detection of lung consolidations with the morphologic features of pneumonia. A PCT assay was performed at presentation, and cut-off of 0.25 and of 0.5 ng/ml were used to rule-out and rule-in pneumonia. The final diagnosis of pneumonia was established by independent clinicians, on the basis of clinical chart review including CT results. Results We enrolled 128 patients and pneumonia was the final diagnosis in 61 (47.7%). In 38 patients (29.7%) LUS and PCT were negative (PCT < 0.25 ng/ml). The overall accuracy, sensitivity and negative predictive value of LUS/PCT were 88.8, 96.7 and 94.7% respectively. Sensitivity of the LUS/PCT test was significantly superior to LUS alone (85.2%) and PCT alone (73.8%) (p < 0.05 for both). Specificity and positive predictive value of the combination of positivity of LUS/PCT (PCT > 0.5 ng/ml) were 94% and 83.3% respectively. Specificity of LUS/PCT was not significantly different to LUS alone (88.1%) (p = 0.125). Conclusions The sensitivity of the combination of LUS with PCT for the diagnosis of pneumonia was significantly superior when compared with the sensitivity of LUS and PCT alone.